RE-PLACING MEMORY: INTERTEXTUAL COLLAGE AND MNEMONIC HISTORIOGRAPHY IN LAKSMISREE BANERJEE’S PEAHEN PASSIONS - Banerjee, Soumyajyoti (ShodhKosh: Journal of Visual and Performing Arts, 2026)
ndian English poetry is frequently characterised by its ability to navigate the tensions between tradition and modernity. Within this poetic landscape, Laksmisree Banerjee’s Peahen Passions (2013), emerges as a fertile site for the exploration of memory as a dynamic, reconstructive force. Banerjee, a distinguished scholar, Fulbright Fellow, and classical vocalist, brings a multidisciplinary sensibility to her craft. She weaves together eco-feminism, postcoloniality, and universal humanism. This investigation expands upon the premise of her poetic practice by applying a rigorous theoretical framework centered on intertextuality and the philosophy of history. By synthesizing the theoretical paradigms of Julia Kristeva, Michael Riffaterre, and Hayden White, the analysis explores how Banerjee re-places memory through an intertextual collage that transcends mere personal recollection to become a metanarrative of internationalism.